In vivo and in vitro immune responses against Francisella tularensis vaccines are comparable among Fischer 344 rat substrains - De Pascalis, Roberto; Bhargava, Varunika; Espich, Scott; Wu, Terry H.; Gelhaus, H. Carl; Elkins, Karen L. (Frontiers in Microbiology, 2023)
Identifying suitable animal models and standardizing preclinical methods are important for the generation, characterization, and development of new vaccines, including those against Francisella tularensis. Non-human primates represent an important animal model to evaluate tularemia vaccine efficacy, and the use of correlates of vaccine-induced protection may facilitate bridging immune responses from non-human primates to people. However, among small animals, Fischer 344 rats represent a valuable resource for initial studies to evaluate immune responses, to identify correlates of protection, and to screen novel vaccines. In this study, we performed a comparative analysis of three Fischer rat substrains to determine potential differences in immune responses, to evaluate methods used to quantify potential correlates of protection, and to evaluate protection after vaccination. To this end, we took advantage of data previously generated using one of the rat substrains by evaluating two live vaccines, LVS and F. tularensis SchuS4-ΔclpB (ΔclpB). We compared immune responses after primary vaccination, adaptive immune responses upon re-stimulation of leukocytes in vitro, and sensitivity to aerosol challenge. Despite some detectable differences, the results highlight the similarity of immune responses to tularemia vaccines and challenge outcomes between the three substrains, indicating that all offer acceptable and comparable approaches as animal models to study Francisella infection and immunity.